The radical innovation affecting competitive advantage of the Thai furniture industry - Tangkit, Kitipong; Panjakajornsak, Vinai (My University, 2017)
Radical innovation has been considered as a main source of competitive advantage for Thai furniture industry which is the important industrial sector that needs creative ideas, skills to increase value added and industrial value. Innovative capability of firms in this industry is also required in order to enable them to survive and prosper in face of increasing both local and foreign competitors. This research aims to develop a structural model of radical innovation and the relevant factors of market orientation, organizational learning, and entrepreneurial orientation affecting competitive advantage of firms in the furniture industry. The populations of this study are the top executives and marketing managers of 4,118 firms in the furniture industry. The research methodologies applied are both in-depth interviews and 7-point Likert scale questionnaires. The result from value of this research will be a structural model of innovation that can be applied to improve competitive advantage of firms in the furniture industry.
Keywords: Competitive advantage; Entrepreneurial orientation; Market orientation; Organization learning; Radical Innovation; Structural equation modeling